2021
DOI: 10.3390/info12090347
|View full text |Cite
|
Sign up to set email alerts
|

DebtG: A Graph Model for Debt Relationship

Abstract: Debt is common in daily transactions, but it may bring great harm to individuals, enterprises, and society and even lead to a debt crisis. This paper proposes a weighted directed multi-arc graph model DebtG of debts among a large number of entities, including individuals, enterprises, banks, and governments, etc. Both vertices and arcs of DebtG have attributes. In further, it defines three basic debt structures: debt path, debt tree, and debt circuit, and it presents algorithms to detect them and basic methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The former finds a cycle with length of exactly c log(|V|) for any constant c, while the latter is of length log(|V|) log(log(|V|)) , provided those exist. Björklund et al [26], however, showed that there does not exist a polynomial time approximation within an approximation ratio of |V| 1− for any unless P = N P. Cui [4] aimed at finding all cycles in a directed graph with the use of classical computing but failed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The former finds a cycle with length of exactly c log(|V|) for any constant c, while the latter is of length log(|V|) log(log(|V|)) , provided those exist. Björklund et al [26], however, showed that there does not exist a polynomial time approximation within an approximation ratio of |V| 1− for any unless P = N P. Cui [4] aimed at finding all cycles in a directed graph with the use of classical computing but failed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the last and biggest instance, we use the debt data (Retrieved from https://figshare.com/articles/dataset/data_txt/14547432/1. (accessed on 10 June 2023)) collected in Huangdao Zone, Shandong Province, China [4]. This graph, as depicted in Figure 3, was decreased in size by deleting all vertices, with an inbound or outbound degree equal to zero and all the corresponding in-/out-arcs.…”
Section: Classic Versus Quantummentioning
confidence: 99%
See 1 more Smart Citation